Fluid Mechanics 1 - Idris, Mat Sahat (Penerbit UMP, 2017)
This module was developed for the purpose of helping students especially for those who are taking fluids mechanics 1 as a subject in Faculty of Mechanical Engineering, Universiti Malaysia Pahang. The target users for this book are the students who have interest in learning more regarding fluid mechanics. In this module, there are many questions with solutions (examples), question to be done by students (on their own will-as practice makes perfect) together with the answers provided. Students always are not certain if their answers to the exercises are correct or not especially for the bright ones. Thus, with the answers included, this will help the students to confirm whether they are on the correct path or not.